Effects of swimming speed on growth and flesh quality of adult Atlantic salmon ( Salmo salar) in closed cages - Zhou, Bingfei (Nord universitet, 2016)
Masteroppgave i havbruk - Nord universitet, 2016 Sperra for utlån til 2021-06-29